1998
DOI: 10.1094/mpmi.1998.11.9.895
|View full text |Cite
|
Sign up to set email alerts
|

Four Classes of Salicylate-Induced Tobacco Genes

Abstract: We have identified and characterized fragments of 15 salicylic acid (SA) early response genes. The kinetics of induction and response to cycloheximide (CHX) treatment allowed classification of genes into four groups. Classes I-III are characterized by immediate-early responses, showing increased accumulation of mRNA within 30 min of SA treatment. Moreover, CHX did not block induction of these genes, indicating that latent cellular factors mediate the SA response. Class IV genes were induced more slowly, but st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
48
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 45 publications
7
48
0
2
Order By: Relevance
“…3a). This behavior was previously reported by us and others in early SAIGs of Arabidopsis and tobacco (Qin et al 1994;Horvath et al 1998;Uquillas et al 2004). As judged by information from public microarray database, it seems to be a common response of a large number of early SAIGs (see response to CHX in Fig.…”
Section: Sa-mediated Activation Of Selected Saigssupporting
confidence: 84%
“…3a). This behavior was previously reported by us and others in early SAIGs of Arabidopsis and tobacco (Qin et al 1994;Horvath et al 1998;Uquillas et al 2004). As judged by information from public microarray database, it seems to be a common response of a large number of early SAIGs (see response to CHX in Fig.…”
Section: Sa-mediated Activation Of Selected Saigssupporting
confidence: 84%
“…To examine whether de novo protein synthesis is involved in ethylene-induced Pti4 function, we blocked protein synthesis by pretreatment of tomato plants with 5 g/mL cycloheximide for 30 min before applying ethylene. Cycloheximide commonly is observed to induce transcription factor genes (Suzuki et al, 1998; Yang and Klessig, 1996;Horvath et al, 1998), and as shown in Figure 2C, it increased Pti4 expression with timing and transcript levels similar to those induced by ethylene. Treatment with a combination of ethylene and cycloheximide further increased the abundance of Pti4 transcripts, possibly as a result of the additive effect of ethylene and cycloheximide.…”
mentioning
confidence: 76%
“…Several transcription factor genes, including tobacco EREBP-1, are immediate-early SA-responsive genes, being activated within 10 min of SA treatment (Horvath et al, 1998). We examined possible effects of SA on Pti4, Pti5, and Pti6 transcript abundance and found, as shown in Figure 3A, that Pti4 transcripts accumulated as early as 30 min after treatment, whereas Pti5 and Pti6 transcript levels were not responsive to SA.…”
Section: Effect Of Cycloheximide On Ethylene Regulation Of the Pti4 Amentioning
confidence: 99%
“…In our previous study, we had mapped the NPR1 interaction domain of NIMIN1 to amino acids 49 to 54 (Weigel et al, 2001). To identify crucial residues within the sixamino acid region that are important for the interaction with NPR1, a rational site-directed mutagenesis approach was taken based on a multiple alignment of the region of three NIMIN proteins (NIMIN1, NIMIN1b, and NIMIN2) (Weigel et al, 2001) and G8-1, a NIMIN-like protein from tobacco (Nicotiana tabacum) (Horvath et al, 1998). Only two consecutive Phe residues are conserved in all four proteins (Phe-49 and Phe-50 in NIMIN1).…”
Section: Npr1 Interacts With Nimin1 But Not With a Mutant Derivativementioning
confidence: 99%